2004
DOI: 10.1051/meca:2004038
|View full text |Cite
|
Sign up to set email alerts
|

Étude de la condensation en film laminaire d'une vapeur pure et saturée sur la paroi poreuse d'une plaque inclinée

Abstract: L'étude en convection forcée de la condensation en film laminaire d'une vapeur pure et saturée sur une plaque poreuse inclinée par rapportà la verticale, est présentée. Le modèle de Darcy-Brinkman est utilisé pour décrire l'écoulement dans le milieu poreux, tandis que leséquations classiques de la couche limite ontété exploitées dans le liquide pur en tenant compte des termes d'inertie et de convection d'enthalpie. Le problème posé aété résolu par voies analytique et numérique. Les résultats sont essentielleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is shown that, in the presence of nanoparticles, the heat transfer is more enhanced in the two-phase model case compared to the one phase model case. A numerical and analytical analysis of the film condensation on the wall of an inclined porous plate was provided by Chaynane et al (2004). The comparison of the Darcy-Brinkman-Forchheimer (DBF) model and the Darcy-Brinkman (DB) model has been treated.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that, in the presence of nanoparticles, the heat transfer is more enhanced in the two-phase model case compared to the one phase model case. A numerical and analytical analysis of the film condensation on the wall of an inclined porous plate was provided by Chaynane et al (2004). The comparison of the Darcy-Brinkman-Forchheimer (DBF) model and the Darcy-Brinkman (DB) model has been treated.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the investigation described in this paper is an extension of the recent work treated by Asbik et al (2002, 2003and Chaynane et al (2004 by supplying an analytical study of thermal dispersion effect during laminar film condensation over Figure 1 schematically shows the condensation process and defines the coordinate system used for the present study. A free stream vapor, at a saturation temperature of T s , flows, over a vertical porous-layer coated surface.…”
mentioning
confidence: 99%